Measuring the Impact on Human Emotion When Listening and Reciting the Quran using AI/Machine Learning Techniques - Nur Asyiqin Hamzah; Hadhrami Ab Ghanni; Azlan Abd Aziz; Nur Hasanah Ali; Noor Zielah Abd Rahman (International Journal of Management and Data Analytics)
The aim of this study is to investigate how the brain responds to the activity of listening and reciting the Quran.  The electroencephalogram (EEG) signals will be utilized as a means to evoke human emotions. The data will be acquired from several participants (subjects) by placing nineteen surface electrodes on the scalp according to the international 10-20 system. The efficacy of the Quran therapy is proposed to be investigated to determine the effect on the brain. There are similar studies conducted and accomplished about 75-89%. As a result, they found that surah Al-Hasyr may help in improving a person’s stress level with beta band dominance to increase their alpha band by increasing balance between both brain hemispheres. However, the result did not suggest that surah Al-Mulk produced a lesser impact since almost all subjects who listened to the surah during the experiment were familiar with the surah and indirectly became less focused on their own recitation. Perhaps, if they paid full attention to the recitation activity, the result could be different. It is also observed that most of the previous work done used a limited number of testing subjects (people who recite/listen to the Quran). Therefore, our empirical study proposed a larger number of testing subjects so that the results would represent more concrete scientific evidence. Our results can be used to draw a conclusion on whether the Quran recitation can be one of the trusted emotional therapy. This can be beneficial to the community, religious institutions, the government, and other stakeholders.